Study on the Structural Plane Characteristics and Disaster-Induced Mechanism of the Yellow River Jingtai Stone Forest, Northwestern Loess Plateau, China - Lyu, Yan; Gu, Gang; Wang, Zuopeng; Leng, Yanqiu; Ma, Penghui; Peng, Jianbing (Frontiers in Earth Science, 2022)
The Yellow River Jingtai Stone Forest (YJSF) is situated in the northwestern margin of the Chinese Loess Plateau, and it is not only one of the most precious and rare types of natural landforms in the Loess Plateau but also a protected area of valuable geological relics and landscapes in northwest China. Massive rock structural planes are present in the stone forest. However, few studies have been conducted on the rock mass structural planes for the slope’s stability. Based on the detailed field investigation, structural planes and their combination types are classified based on the rock mass. On this basis, combined with physical, mechanical, and hydraulic tests, the disaster-induced mechanism of the rock mass structural planes is classified and discussed. Results show that the structural planes of the YJSF can be divided into three types, namely, the primary structural plane, tectonic structural plane, and secondary plane. They not only combine with each other to cut the rock mass into different shape blocks but also jointly control the stability of the rock mass slope. The physical and mechanical tests and water sensitivity characteristics show that the conglomerates and muddy sandstones which are the main components of the YJSF have strong tensile and shear strengths under natural situations, while their strengths are reduced under immersion infiltration; in particular, the muddy sandstones are more sensitive to water and have a lower strength than that of the conglomerates. Finally, the disaster-induced mechanism of the YJSF is mainly related to the combination of various structural planes, which can be divided into four failure patterns, namely, creeping slide-tension failure, gradual failure, slipping failure, and dumping failure; coupling action of endogenic and exogenic geodynamic processes was responsible for their formation. The studied results will provide critical, theoretical, and technical support for the slope stability analysis, scenic geological heritage protection, and disaster warning in this area.